Learning Organization Strategy in the Face of Covid-19 with The Fifth Discipline Approach - Ivan Yulivan; Stepi Anriani (GoAcademica Research & Publishing, 2022)
This study aimed to determine the strategies of learning organizations in dealing with the Covid-19 pandemic. This study uses a post-positivism approach with qualitative methods. Data was collected through in-depth interviews with informants from four companies analyzed online. Based on the data and analysis results, it can be concluded that the company has demonstrated the application of several disciplines from the fifth discipline approach. These four organizations have not fully implemented the five disciplines; some companies carry out 2 or 3 sentences from Peter Senge. Each company applies its methods and strategies, and all four can survive the Covid 19 pandemic.